Rancang Bangun Sistem Informasi Apotek Berbasis Client Server Pada Apotek An Nur Kotabumi - Haliq Haliq; Ferry Susanto (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2019)
An Nur Kotabumi Pharmacy is one of the pharmacies that sell and have a large stock of medicines. All transactions that occur at the pharmacy are still recorded manually, namely by recording the transaction into a book. Some transactions carried out include drug sales transactions to consumers whether sales of prescriptions or non-prescriptions are still recorded manually in a book. Based on these problems, an application is needed to manage and process drug data so that the transaction process can be carried out properly. Applications that are used must also be computerized well in order to reduce errors in the transaction data collection process and can be used by many computers so that it is more effective when inputting drug data. This is because of the large number of drugs and transactions that occur, a well-integrated database is needed so that it will greatly support the performance of employees who interact directly with the system.